2005
DOI: 10.1007/s11270-005-7272-1
|View full text |Cite
|
Sign up to set email alerts
|

Lysimeter Study on the Effects of Different Rain Qualities on Element Fluxes from Shallow Mountain Soils in Southern Norway

Abstract: This study focuses on fluxes of elements from, and changes in the soil properties of shallow organic material rich soil as a result of changes in precipitation acidity. Intact soil columns including natural vegetation from two areas (one exposed to acidic precipitation and one unpolluted) were used in a lysimeter experiment. The lysimeters were watered with simulated normal rain (pH 5.3) or simulated acidic rain (pH 4.3) for four years. Sulphuric acid and ammonium nitrate were used to regulate the quality of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A geometrid moth outbreak 'rarely causes noticeable defoliation at more southern latitudes' in Norway (Neuvonen et al 2005, 126) and forest fires have not been reported in the study area 262 A. Bryn NORSK GEOGRAFISK TIDSSKRIFT 62 (2008) from the 20th century. The only notably exception was a slightly reduced nitrogen downfall (Strand et al 2005) and an increased elk population (Solberg et al 2006). Both factors can constrain the speed of forest regeneration, but cannot change its prevailing direction.…”
Section: The Biophysical Cultural Landscape and Natural Dynamicsmentioning
confidence: 99%
“…A geometrid moth outbreak 'rarely causes noticeable defoliation at more southern latitudes' in Norway (Neuvonen et al 2005, 126) and forest fires have not been reported in the study area 262 A. Bryn NORSK GEOGRAFISK TIDSSKRIFT 62 (2008) from the 20th century. The only notably exception was a slightly reduced nitrogen downfall (Strand et al 2005) and an increased elk population (Solberg et al 2006). Both factors can constrain the speed of forest regeneration, but cannot change its prevailing direction.…”
Section: The Biophysical Cultural Landscape and Natural Dynamicsmentioning
confidence: 99%
“…There is also evidence of variation in tundra or alpine soil Al and Fe being linked to topography, with higher Al and Fe concentrations e.g. at the bottom of a hill slope or in depressions (Litaor 1992;Ping et al 1998;Strand et al 2005) or related to soil age (Giblin et al 1991). Whether inherent differences in the distribution of Al and Fe also can affect P availability in tundra ecosystems still remains unknown; we do, however, believe that accumulation of Al and Fe in organic soils might be a factor that hitherto has been overlooked.…”
mentioning
confidence: 99%
“…This does not seem to be the case in Froan, and Molinia caerulea has not yet been registered in Froan (Moen et al 2006b;Bryn 2008a). Moreover, the last decades of industrial legislations to hinder acid rain have actually reduced the nitrogen pollution over Norway during recent years (Strand et al 2005), although the long-term response of reversed pollution is still unclear (Terry et al 2004;Holden et al 2007).…”
Section: Discussionmentioning
confidence: 99%